Science Learning Using the Jigsaw Strategy to Improve Primary School Student Learning Outcomes - Abdul Kadir; Rahmaini (Yayasan Zia Salsabila, 2024)
Previous studies have indeed discussed jigsaw strategies from various scientific aspects, but the differences in setting, time and methods in this research are new aspects that are revealed in depth. This research aims to analyze science learning using the jigsaw strategy to improve elementary school students' learning outcomes. This is intended to develop students' potential in a collaborative, cooperative and radical way through direct learning experiences using jigsaw active learning strategies. From the results of this research it can be concluded that the learning process in elementary schools using the jigsaw method can improve student learning outcomes, by meeting the minimum completeness criteria and the increase in student learning outcomes can be seen from each cycle. Thus, learning using the jigsaw strategy is effectively applied to science learning for elementary school students.